Your practicum in psychology : a guide for maximizing knowledge and competence - Matthews, Janet R.; Walker, C. Eugene (Clarence Eugene), 1939- (American Psychological Association, 2015)
"A psychology student's practicum placement experience has the potential to be the most exciting time in his or her graduate training. This comprehensive guide to the practicum is a vital guide for all students beginning their field placement, and for those curious about how the system works. In conversational and accessible language, the authors equip students with the knowledge they need to anticipate, prevent, and resolve common difficulties that may arise during practicum placement. Readers will find helpful background information on finding one's feet, developing rapport with clients, confidentiality and ethics, symptoms of psychopathology, assessment, psychopharmacology, and working with children or older adults. This second edition includes new and updated chapters that will appeal to all graduate students and advanced undergraduates"--Publicity materials. (PsycINFO Database Record (c) 2015 APA, all rights reserved)